2013
DOI: 10.1111/emr.12072
|View full text |Cite
|
Sign up to set email alerts
|

Ethical consideration in invasion ecology: A marine perspective

Abstract: Summary Biological introductions of species to regions outside their known natural distribution are considered a major threat to native marine biodiversity and a key consideration for ecological management. For most invasive species in marine systems, however, little is known about potential impacts. If we are to increase our knowledge of the processes and mechanisms behind the spread of nonindigenous species or determine economic or ecological impacts, manipulative ecological field experiments are the best wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 72 publications
(146 reference statements)
0
4
0
Order By: Relevance
“…This zonation pattern in the bay greatly contrasts with that observed in mid-intertidal fringes on other parts of the Chilean coast, where in the absence of the tunicate s, the mussel dominates the mid-intertidal primary substratum [1] , [31] , [32] . Environmental and ethical constraints [33] , [34] have prevented us from undertaking large-scale removals (dozens or hundreds of meters) of tunicate or mussel inside the bay to test at a large-scale the inter-specific competitive hypothesis. Instead, we carried out small-scale manipulative and transplant field experiments, in caging units of less than 400 cm 2 , to test the competition strength and survival between P. praeputialis and P. purpuratus [18] , [30] .…”
Section: Introductionmentioning
confidence: 99%
“…This zonation pattern in the bay greatly contrasts with that observed in mid-intertidal fringes on other parts of the Chilean coast, where in the absence of the tunicate s, the mussel dominates the mid-intertidal primary substratum [1] , [31] , [32] . Environmental and ethical constraints [33] , [34] have prevented us from undertaking large-scale removals (dozens or hundreds of meters) of tunicate or mussel inside the bay to test at a large-scale the inter-specific competitive hypothesis. Instead, we carried out small-scale manipulative and transplant field experiments, in caging units of less than 400 cm 2 , to test the competition strength and survival between P. praeputialis and P. purpuratus [18] , [30] .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, an experimental study by Borsje et al (2011) found that nonnative oyster beds were more effective in wave attenuation than were native mussel beds. Nonnative species, however, should not be introduced for shoreline protection purposes if they are not already naturalised in the targeted environment, or if their presence will lead to negative ecological or socioeconomic impacts that outweigh their benefits (Bunting & Coleman 2014). Ultimately, the habitat-forming species need to be self-sustaining.…”
Section: Soft Approaches and The Selection Of Habitat-forming Speciesmentioning
confidence: 99%
“…In the study of invasive species, the ability to examine molecular processes associated with phenotypically plastic responses (e.g., through environmentally driven gene expression differences) and those indicative of local adaptive evolution (e.g., through changes in allele frequencies) is often limited by the relative lack of background genetic data available, particularly for non-model species [16]. Examining these two processes can be further complicated when traditional methods used to assess local adaptation, such as reciprocal translocation experiments, bring up ethical concerns since moving invasive populations to new locations may increase their potential spread [17]. This concern may be especially true for highly prolific invasive species.…”
Section: Introductionmentioning
confidence: 99%